Quantitative Detection of Hepatitis B Virus DNA by Real-Time Nucleic Acid Sequence-Based Amplification with Molecular Beacon Detection - Yates, Sol (American Society for Microbiology, 2001)
We have developed a hepatitis B virus (HBV) DNA detection and quantification system based on amplification with nucleic acid sequence-based amplification (NASBA) technology and real-time detection with molecular beacon technology. NASBA is normally applied to amplify single-stranded target RNA, producing RNA amplicons. In this work we show that with modifications like primer design, sample extraction method, and template denaturation, the NASBA technique can be made suitable for DNA target amplification resulting in RNA amplicons. A major advantage of our assay is the one-tube, isothermal nature of the method, which allows high-throughput applications for nucleic acid detection. The homogeneous real-time detection allows a closed-tube format of the assay, avoiding any postamplification handling of amplified material and therefore minimizing the risk of contamination of subsequent reactions. The assay has a detection range of 10(3) to 10(9) HBV DNA copies/ml of plasma or serum (6 logs), with good reproducibility and precision. Compared with other HBV DNA assays, our assay provides good sensitivity, a wide dynamic range, and high-throughput applicability, making it a viable alternative to those based on other amplification or detection methods.